2017
DOI: 10.1038/srep42809
|View full text |Cite
|
Sign up to set email alerts
|

Identification of miRNA-mRNA Modules in Colorectal Cancer Using Rough Hypercuboid Based Supervised Clustering

Abstract: Differences in the expression profiles of miRNAs and mRNAs have been reported in colorectal cancer. Nevertheless, information on important miRNA-mRNA regulatory modules in colorectal cancer is still lacking. In this regard, this study presents an application of the RH-SAC algorithm on miRNA and mRNA expression data for identification of potential miRNA-mRNA modules. First, a set of miRNA rules was generated using the RH-SAC algorithm. The mRNA targets of the selected miRNAs were identified using the miRTarBase… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
8
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 104 publications
(108 reference statements)
1
8
0
Order By: Relevance
“…Such studies usually also perform miRNA–mRNA pair selection based on miRNA–mRNA interaction experimental databases or prediction algorithms, functional enrichment analyses of the genes or proteins, disease association, and other analyses in order to relate the miRNA and mRNAs in modules to the cancer types/subtypes of interest or survival probability. Specifically, in a study of colorectal cancer, the rough hypercuboid based supervised clustering algorithm (RH-SAC) was used to generate clusters of functionally similar miRNAs or mRNAs whose coherent expression can further efficiently classify the samples [29]. In a study of multiple myelomas, through integrative analysis of GO biological processes, miRNA–mRNA targeting relationship, and matched miRNA and mRNA expression data, the ping-pong algorithm and multiobjective genetic algorithm were integrated to detect subtype-specific miRNA–mRNA regulatory modules [30].…”
Section: Discussionmentioning
confidence: 99%
“…Such studies usually also perform miRNA–mRNA pair selection based on miRNA–mRNA interaction experimental databases or prediction algorithms, functional enrichment analyses of the genes or proteins, disease association, and other analyses in order to relate the miRNA and mRNAs in modules to the cancer types/subtypes of interest or survival probability. Specifically, in a study of colorectal cancer, the rough hypercuboid based supervised clustering algorithm (RH-SAC) was used to generate clusters of functionally similar miRNAs or mRNAs whose coherent expression can further efficiently classify the samples [29]. In a study of multiple myelomas, through integrative analysis of GO biological processes, miRNA–mRNA targeting relationship, and matched miRNA and mRNA expression data, the ping-pong algorithm and multiobjective genetic algorithm were integrated to detect subtype-specific miRNA–mRNA regulatory modules [30].…”
Section: Discussionmentioning
confidence: 99%
“…Statistical approaches use statistical tests to find significant modules ( Liu et al, 2010 ; Jayaswal et al, 2011 ; Yan et al, 2012 ; Hecker et al, 2013 ). Rule induction approaches use machine-learning methods to search for subgroups ( Tran, Satou & Ho, 2008 ; Song et al, 2015 ; Paul et al, 2017 ). Probability-based approaches either use population-based probabilistic learning or probabilistic graphical model to infer regulatory information ( Joung et al, 2007 ; Joung & Fei, 2009 ).…”
Section: Introductionmentioning
confidence: 99%
“…(5). Some studies have demonstrated the abnormally high expression of miR-93-5p in liver (6), breast (7) and lung cancer (8), and it is able to promote cell proliferation and migration by binding to various target genes. Moreover, it has been reported that miR-93-5p may be a potential biomarker for the detection of the presence of cancer (9).…”
Section: Introductionmentioning
confidence: 99%